Emerging treatments for urinary incontinence. (June 2014) - Polland, Allison; Mock, Stephen; Dmochowski, Roger R
<x xml:space="preserve">Abstract</x> Introduction: Urinary incontinence (UI) is a common and distressing problem that can adversely affect a patient's quality of life. Medical treatment is integral in the management of UI, of which there are a number of novel therapeutic targets. Areas covered: In this review, an overview of UI and its associated burden on patients and on the healthcare system is provided. While there are many options for therapy currently available, the focus of this review is emerging therapies that may contribute in the near future to the management of UI. Expert opinion: Healthcare expenditures for diagnosis, evaluation and treatment are substantial and are increasing as the general population ages and as access to healthcare increases. Pharmacological therapy for stress UI is limited and autologous muscle-derived cell therapy holds great promise. Despite the myriad of antimuscarinics for urge UI, all those presently FDA approved have comparable efficacy and adverse events, despite advertisements that suggest otherwise. Antimuscarinics and β agonists are likely to remain mainstays of treatment as agents that act on novel targets such as transient receptor potential vanilloid type 1 and neurokinin-1 require further study.